PEMBUATAN ARANG AKTIF DARI SERBUK GERGAJI SENGON UNTUK PENJERNIH AIR - Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Experimental study on Paraserianthes falcataria sawdust to produce activated charcoal for water treatment is reported in this paper. The purpose of this research is to study the effect of raw material treatment and chemical addition on the activated charcoal yield and quality.The result shows that the yield of activated charcoal range from 22.88 - 35.98 %, moisture content from 1.43 - 5.85%, volatile matter from 9.16 - 15.39 %, fixed carbon from 60,90 - 75.33 %,.ash content from 15.51 - 23.71 % and silica from 8.89- 13.69%.The adsorptive capacity of iodine, benzene and sulfuric acid respectively range from 444.26 - 761.40 mg/g, 1.23 - 8.83 % and 17.40 -35.26 %. Good quality of the activated charcoal was produced from charcoal of sengon sawdust with sodium carbonate as activator. This is especially for the adsorptive capacity of iodine where this criteria has met the commercial standard requirement of the Americoal Water Work Association and the Indonesian Industrial Standard.The quality of water after treatment with the activated charcoal shows that the iron (Fe) content range from 0.00 - 0.09mg/1, calsium (Ca) from 3.35 - 22.66 mg/1, sodium (Na) from 8.80 - 9340.0mg/1, mangan (Mn) from 0.00 - 0.08mg/1, nicel (Ni) from 0.03 - 0.77mg/1, chloride (Cl) from 21.0 - 170.0mg/1, ammonium (NH4) from 0.00 - 0.44 mg / 1 and chemical oxygen demand (COD) range from 21.40 - 61.20 mg / 1